HSV Keratitis: Histopathologic Predictors of Corneal Allograft Complications - Shtein, Roni M. (The American Ophthalmological Society, 2008)
PURPOSE: To identify histopathologic features predictive for adverse allograft outcomes following penetrating keratoplasty for herpes simplex virus (HSV) keratitis. METHODS: Retrospective, interventional case series of 62 consecutive patients with HSV keratitis who underwent penetrating keratoplasty at the Kellogg Eye Center from 1990 through 2000. A detailed chart review and review of the histopathology of the excised corneal button were performed to identify associations between clinical data (disease activity, vascularity, adverse allograft outcomes) and histopathologic data (inflammation, neovascularization, biomarkers). The main outcome measure was to find histopathologic features that may predict HSV recurrence, allograft rejection, or failure. RESULTS: Although 81% of patients had clinically quiescent disease, histopathology revealed that 74% had active corneal inflammation, a finding that was associated with the presence of clinical neovascularization (P = .01). Histopathologic inflammation was a risk factor for allograft rejection (P = .02) but not failure (P = .98) or HSV recurrence (P = .45). Histopathologic neovascularization did not predict rejection (P = .19) but did predict failure (P = .002) and HSV recurrence (P = .05). Biomarkers, including HLA-DR, ICAM-1, and IL-8(CXC) and MCP-1 (CC) chemokines, were all significantly increased in fresh corneal specimens demonstrating moderate to severe inflammation. IL-10 treatment ex vivo significantly inhibited HLA-DR, IL-8 (P = .006), and MCP-1 (P = .01) but did not reduce ICAM-1 expression. CONCLUSION: Histopathologic inflammation, neovascularization, and the presence of specific biomarkers are risk factors for corneal allograft morbidity.